Multivariat Analysis Of Variance (MANOVA) Di Bidang Kesehatan Dan Pendidikan MIPA - Indarini Dwi Pursitasari; Bibit Harianto; Sinta Srie Wulan; Dody Hermanto; Didit Ardianto (Jurnal Ilmiah Kanderang Tingang, 2024)
Multivariate Analysis of Variance (MANOVA) is a quantitative data analysis technique to determine the significance of differences in more than two means of dependent variables. The Manova requirements test includes multivariate normality test with Mardia test and covariance matrix homogeneity test with Box's M test. There are several Manova test statistics, namely Wilks' Lambda, Pillai, Lawley-Hotelling, and Roy's Largest Root. The difficulty of multivariate analysis in calculations that are too complicated has been solved by the existence of statistical software that is increasingly sophisticated, so that it is able to explain the changes or effects of the treatment given and its interactions.The purpose of this study is to analyze the use of Manova in MIPA and health education research. The method used is literature review. The results showed that the use of Manova test in Thus, although both involve scientific approaches and data analysis, health and education research have different methodological characteristics and variable focus.